(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2024)
Milk and dairy products are potentially contaminated with aflatoxin M1 (AFM1), especially in tropical and subtropical regions like Malaysia. This study aimed to detect the concentration of AFM1 in raw cow milk samples by ELISA method. A total of 46 samples of raw cow milk were received from four Milk Collection Centres (MCC) in Perak (A, B, C and D). 13.0% of the samples examined were found to exceed the European Commission (EC) 0.05 µg/kg maximum limit, with samples from MCC B and D accounting for 25.0% and 21.1% respectively. Statistical analysis showed that there was a significant difference in the mean concentration of AFM1 between the four MCCs at p<0.05. Among all these MCC groups, MCC A-B showed that there was a significant difference in concentration of AFM1 mean value at p<0.0125, while other groups of MCC groups were not significantly different. Nevertheless, all AFM1 concentration values in this study were below the 0.5 µg/kg limit set by the Food Act 1983 (Act 281) & Food Regulation (1985). However, the low concentration of aflatoxin observed in this study does not guarantee its absence in the future. Therefore, improvements especially in the process of handling and storing livestock feed and products (milk and meat) as well as consistent monitoring for the presence of aflatoxin to reduce the risk of aflatoxin toxicity to consumers.